Antiseptic and Disinfectant Utilization Patterns at Tlemcen University Hospital Center: A Five-Year Epidemiological Study - Amel Berrached; Hafida Hassaine; Fethi Borsali; Nezha Bereksi Reguig Berber; Amel Chiali; Lamia Boublenza; Zatla, Ilyes (Journal of Public Health and Pharmacy, 2025)
Introduction: Disinfectants and antiseptics are integral components of hospital infection control policies; however, their overuse can lead to microbial resistance, a growing concern in healthcare settings. This study aims to analyze the consumption patterns of antiseptics and disinfectants across various departments of Tlemcen University Hospital Center (CHU), providing insights into their usage over a five-year period and helping inform strategies for more responsible use. Methods: Data on the consumption of Povidone iodine (PVI) and various disinfectants across 20 departments over a five-year period (2015–2019) were obtained from the pharmacy and relevant CHU departments. Statistical analysis was conducted using SPSS version 25. Chi-square tests were employed to compare categorical data, and ANOVA was used to assess trends in consumption over time. Results: The results revealed a decline in PVI consumption to 13.5% in 2019, while disinfectant use increased by 29.1%, possibly due to a reduction in surgical procedures and an increase in medical admissions. Notably, consumption patterns varied across departments, with surgical services showing higher disinfectant use compared to medical services. Conclusion: Given the extensive use of antiseptics and disinfectants, we recommend implementing strategies to reduce their overuse, such as periodic audits of antimicrobial consumption and educational programs for healthcare professionals to mitigate the risk of microbial resistance.